Generative Artificial Intelligence Utilization and Productivity Among English Teachers in Selected Private Higher Education Institutions in Laguna - Delos Reyes, Myreen Rose; Juanita Corre (International Journal on Integrated Education, 2025)
The integration of Generative Artificial Intelligence (AI) in education has emerged as a transformative force in instructional methodologies, particularly in English language teaching. This study examined the impact of generative AI tools on the productivity of English language teachers in selected private higher education institutions in Laguna, Philippines. With the rapid advancement of educational technologies, especially AI-driven platforms, the research aimed to assess the extent of AI utilization, frequency of use, training received by educators, and how these factors influenced instructional efficiency, time management, student engagement, and learning outcomes. A quantitative research design was utilized, and data were collected through a survey questionnaire administered to 30 English teachers from various private institutions. The data were analyzed using descriptive and inferential statistical methods.Grounded in the theory of Technological Determinism, the research employed a quantitative correlational design to determine the relationship between AI usage and teacher productivity. The findings revealed a moderate positive correlation (r = 0.409, p = 0.025) between AI utilization and productivity, indicating that teachers who actively integrated AI tools experienced improved lesson planning efficiency, greater student interaction, and better academic outcomes. The study further emphasized the critical role of adequate training in maximizing the potential of generative AI, as well-trained teachers were found to implement AI more effectively and confidently. Moreover, the results were consistent with global research that highlights AI’s capacity to support personalized learning, reduce administrative workload, and enhance adaptive instruction. Despite these benefits, challenges such as insufficient institutional support, lack of clear policy frameworks, and limited digital literacy were identified. Therefore, the study recommended implementing comprehensive training programs, developing ethical guidelines and policies, and investing in digital infrastructure to support AI integration. Finally, this research contributed valuable insights to the evolving discourse on educational technology and serves as a guide for institutions and policymakers aiming to enhance teaching practices through AI.